Vaginal birth after cesarean. - Acosta, Manuel (2015)
Objectives; To study the incidence of vaginal deliveries following cesarean section and observe repercussions on maternal and perinatal morbidity and mortality, characteristics of labor curves, complications, hospitalization time and hospital costs. Method: Retrospective study of 21646 deliveries attended during 1991. The group study was alleatory, considering month by month. Results: Two thousand one hundred and forty one patients with previous cesarean section were admitted: 1489 (69,4%) were attended per vaginal route and 652 (30,6%) by cesarean section. The group study was selected from the 1489 vaginal deliveries; 98% had spontaneus normal vaginal delivery and 2% vacuum delivery; 96% had one previous cesarean section, 3% two previous cesarean section and 1% three previous cesarean sections. Period between deliveries was less than 24 months in 18% and over 48 months in 42%. Conclusion: Attention of vaginal delivery following history of cesarean section may be encouraged in higher level health institutions with appropriate conditions and resources. in order to diminish cesarean section rates, hospitalization days and costs.